Delivery Room Breastfeeding for Prevention of Hypoglycaemia in Infants of Diabetic Mothers. (1st February 2014) - Maayan-Metzger, Ayala; Schushan-Eisen, Irit; Lubin, Daniel; Moran, Orit; Kuint, Jacob; Mazkereth, Ram
<x xml:space="preserve">Abstract</x> Objective: To evaluate the effect of duration of early breastfeeding in the delivery room on blood glucose levels among term neonates of diabetic mothers. Methods: Mothers with gestational diabetes were encouraged to breastfeed their infants immediately after birth in the delivery room. The breastfeeding duration was recorded by the midwife. Results: The longer duration of breastfeeding subgroup (n = 39) demonstrated a lower rate of hypoglycaemia in the first 8 hours of life (< 40 mg/dl) compared to the shorter duration subgroup (n = 40), but this difference did not reach statistical significance (2.6% vs. 17.5% respectively, p = 0.057). Hypoglycaemia was mainly predicted by lower cord glucose for each decrease of 10 mg/dl (OR 2.11 [CI 1.1–4.03] p = 0.024. Conclusion: Longer duration of delivery room breastfeeding did not reduce the rate of hypoglycaemia, which was mainly influenced by lower cord blood glucose level.